Pengaruh Investment Experience, Financial Behaviour, dan Risk Tolerance terhadap Keputusan Investasi pada Instrumen Keuangan Hijau - Hikmah Hikmah; Muhammad Haldy; Helmi Toatubun (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
This study aims to analyze the influence of investment experience, financial behaviour, and Risk Tolerance on investment decisions in green financial instruments within the context of sustainable finance. A quantitative approach was employed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS software. Data were collected through an online survey using a purposive sampling technique, involving 204 respondents who are active investors. The results indicate that investment experience has a significant effect on both investment decisions and Risk Tolerance, suggesting that experience enhances individuals’ ability to understand risks and opportunities in green investments. In addition, financial behaviour significantly influences investment decisions and Risk Tolerance, highlighting the importance of sound financial management in supporting rational and well-planned investment decisions. Furthermore, Risk Tolerance has a significant impact on investment decisions, indicating that an individual’s level of Risk Tolerance plays a crucial role in selecting appropriate investment instruments. Overall, the findings suggest that improved investment experience and positive financial behaviour strengthen individuals’ Risk Tolerance, which ultimately leads to more optimal investment decisions in green financial instruments.